2012
DOI: 10.5194/esdd-3-1085-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A GIS based study on bank erosion by the river Brahmaputra around Kaziranga National Park, Assam, India

Abstract: The Kaziranga National Park is a forest-edged riverine grassland inhabited by the world's largest population of one-horned rhinoceroses, as well as a wide diversity of animals. The park is situated on the southern bank of the Brahmaputra River at the foot of the Mikir Hills. National Highway 37 forms the southern boundary and the northern boundary is the river Brahmaputra and covers an area of about 430 km<sup>2</sup>. The Brahmaputra River flows by Kaziranga National Park in a braided course for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…In a previous study of the Diana river, the authors have found almost similar processes of bank erosion at its lower courses (Chakraborty and Mukhopadhyay, 2014). At a regional scale the observed bank erosion processes are more or less similar to the processes of bank failure documented along the Brahmaputra river (Kotoky et al, 2005;Dutta et al, 2010;Sarma and Acharjee, 2012) and Ganga river (Thakur et al, 2012); while at broad global scales this resembles although to a little extent to the processes operating along the Devonian streams (Hooke, 1979), the Swale-Ouse river system (Lawler et al, 1999), and the Nile river (Ahmed and Fawzi, 2011) etc. More or less similar effects of riparian vegetation on bank erosion of the Duduya river makes us capable of connecting it to the Central Sacramento River of California (Micheli et al, 2004) and to the Daintree and other tropical rivers of Queensland, Australia (Bartley et al, 2008).…”
Section: Discussionsupporting
confidence: 58%
“…In a previous study of the Diana river, the authors have found almost similar processes of bank erosion at its lower courses (Chakraborty and Mukhopadhyay, 2014). At a regional scale the observed bank erosion processes are more or less similar to the processes of bank failure documented along the Brahmaputra river (Kotoky et al, 2005;Dutta et al, 2010;Sarma and Acharjee, 2012) and Ganga river (Thakur et al, 2012); while at broad global scales this resembles although to a little extent to the processes operating along the Devonian streams (Hooke, 1979), the Swale-Ouse river system (Lawler et al, 1999), and the Nile river (Ahmed and Fawzi, 2011) etc. More or less similar effects of riparian vegetation on bank erosion of the Duduya river makes us capable of connecting it to the Central Sacramento River of California (Micheli et al, 2004) and to the Daintree and other tropical rivers of Queensland, Australia (Bartley et al, 2008).…”
Section: Discussionsupporting
confidence: 58%
“…The Asian picture of riverbank erosion and displacement is particularly bad due to these countries' higher population density. Historically, riverbank erosion in the lower Mekong basins (see Miyazawa et al, 2008), the Yellow River (Huang He) erosion in China (see Ma et al, 2012), the Irrawaddy and Chindwin rivers in central Myanmar and the River Ganges and Brahmaputra in India caused massive landscape degradation displacing millions of people (Sarma & Acharjee, 2012;Mili et al, 2013).…”
Section: Migration and Displacement In Hazard Researchmentioning
confidence: 99%
“…The BR is well known for its dynamic hydro-geomorphic characteristics (Coleman, 1969;Kotoky et al, 2005;Sarma & Acharjee, 2012;Sarma & Phukan, 2006). Owing to its braidedness and instability accompanied by huge sediment transport, the multi-channels of the BR push its bankline laterally instigating bank erosion (Coleman, 1969).…”
Section: Bankline Migrationmentioning
confidence: 99%